2014
DOI: 10.1007/s13595-014-0392-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mechanical strength of particleboard using environmentally friendly pine (Pinus pinaster L.) tannin adhesives with cellulose nanofibers

Abstract: International audienceContext Condensed tannins have been successfully used as substitutes for phenol in the production of resins for wood products. However, the enhancement of the properties of tannin-based resins with nontoxic and cost effective additives is of great interest.• Methods In the present work, the performance enhancement of tannin-based particleboards with cellulose nanofibers was investigated.• Results In presence of 2 % of cellulose nanofibers, the viscosity of tannin-based adhesives and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 27 publications
(27 reference statements)
3
28
1
3
Order By: Relevance
“…Hypothetically if these fines were removed, the enhancement of mechanical properties provided by CNF would be more significant and, consequently, the saturation level for CNF would also be superior. This result is in agreement with those obtained by Cui et al (2014) on particleboard made of Pine (Pinus pinaster L.), where the board at 2 wt% of CNF was the strongest. In our study, while the modulus of rupture (MOR) was constant after 2 wt% of CNF, the modulus of elasticity (MOE) kept improving until 8 wt% of CNF.…”
Section: Mechanical Characterizationsupporting
confidence: 92%
“…Hypothetically if these fines were removed, the enhancement of mechanical properties provided by CNF would be more significant and, consequently, the saturation level for CNF would also be superior. This result is in agreement with those obtained by Cui et al (2014) on particleboard made of Pine (Pinus pinaster L.), where the board at 2 wt% of CNF was the strongest. In our study, while the modulus of rupture (MOR) was constant after 2 wt% of CNF, the modulus of elasticity (MOE) kept improving until 8 wt% of CNF.…”
Section: Mechanical Characterizationsupporting
confidence: 92%
“…Different fracture circumstances may occur, as shown in Fig. 3b: (i) material under force; (ii) cohesive failure indicating that the adhesive may need strengthening; (iii) the possibility of interfacial failure due to poor interaction between materials and adhesives; and (iv) material failure occurring before the adhesives fracture (River et al 1991;Comyn 1997). This was due to the adhesive layer being very thin, and close attachment caused by deep adhesive penetration and planed wood surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Veigel et al (2012) published another study on UF and melamine-ureaformaldehyde (MUF) adhesives in a matrix of adhesive resins and CNF while using ammonium nitrate in water solutions as a hardener for particleboard and oriented strand board, which showed increased values of fracture energy and toughness (Veigel et al 2012). Cui et al (2015) similarly reported improved strength in particleboard when a tannin cross-linked adhesive system was supported by microfibrillar cellulose in the presence of solid paraformaldehyde as the hardener. Mahrdt et al (2016) published a follow-up paper to Veigel et al (2012), showing the effect of adding microfibrillar cellulose and aqueous ammonium nitrate as a hardener to UF resins for particleboards.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cement-bonded composites, gypsum-bonded sawdust composites generally contain a high percentage of gypsum in the product. They have some limitations, such as low mechanical performance, low durability, and bad compatibility (Lei et al, 2006;Kang et al, 2012;Cui et al, 2014) with sawdust. Moreover, they have got less attention compared to cement-bonded composites.…”
Section: Introductionmentioning
confidence: 99%
“…His team has also used a mixed hardwood-softwood fibres for the composite development. Nanomaterials, such as SiO 2 (Lei et al, 2006) and cellulose nanofiber (Cui et al, 2014), have also been used to reinforce gypsum-bonded sawdust composites, indicating that the addition of nano-material could increase the mechanical performance of gypsum-bonded sawdust composites significantly. In addition, a promising report from Henke and Treml (2013) showed that additive manufacturing of large scale solids can be achieved by using sawdust and gypsum in 3D printing processes.…”
Section: Introductionmentioning
confidence: 99%